Programming Arduino projects with the PIC microcontroller : a line-by line code analysis and complete reference guide for embedded programm - Ward, Hubert Henry (Apress, 2022)
Now that youve built a few Arduino projects, and reused some pre-written sketches, its time to move on to the next step and explore the world of embedded programming. To truly up-skill, you'll need to understand how your code works, and that's where this book comes in. You'll review and work with several Arduino projects plus two extra ones written for a PIC microcontroller. Each one is accompanied with a basic circuit diagram and photos of the program working. Ideal for the Arduino hobbyist and PIC programmers who want to merge their skills, this comprehensive book will go over every aspect of the 8-bit microcontroller, provide line-by-line analysis of the code, and in the end, show you how to bring your Arduino projects to the PIC microcontroller using C. You'll gain a full understanding of how the C instructions work and can be used with the PIC microcontroller. Programming Arduino Projects with the PIC Microcontroller is your one-stop reference resource. You will: Examine how the code works Create code to perform any function Build practical projects on vero boards with full vero plans and circuit diagrams Understand how programs work by simulation with an ECAD package.